Pelatihan Penyusunan Instrumen Evaluasi Bahasa Indonesia Berbasis Nilai-Nilai Kecakapan Abad 21 - Imam Safi’i; Wini Tarmini; Andi Wibowo; Sobri Sobri (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING ON DEVELOPING INDONESIAN LANGUAGE EVALUATION INSTRUMENTS BASED ON 21ST CENTURY SKILLS VALUES. This article aims to describe the training activities for the preparation of an evaluation instrument based on 21st century skill values for teachers of SDN Gandaria Selatan 01 Jakarta Selatan. An evaluation instrument based on 21st century skills values is an evaluation instrument developed based on the development of critical thinking, creative-innovative, collaborative, and communicative. The procedure used in this training activity is to use the pedagogical model of the genre, namely through the activities of building context, examining models, constructing together, and constructing independently. The technical evaluation instrument preparation was carried out using google assessment media. This training activity was able to improve the professional competence of teachers at SDN Gandaria Selatan 01 Jakarta Selatan in developing evaluation instruments based on 21st century skill values.